2020
DOI: 10.1111/ijcp.13849
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to erectile dysfunction treatment via pharmacies to improve healthcare provider visits and quality of life: Results from a prospective real‐world observational study in the United Kingdom

Abstract: Objectives The Medicines and Healthcare Products Regulatory Agency in the United Kingdom (UK) formally reclassified sildenafil citrate 50 mg tablets as a pharmacy medicine (sildenafil‐P) in 2017 for adult men with erectile dysfunction (ED). A 1‐year prospective real‐world observational study was conducted to track men's health behaviour, particularly their healthcare resource utilisation (HCRU) and quality of life (QoL) before and after the availability of sildenafil‐P. Methods Adult men with ED aged ≥18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Total of 14.8 percent of men in our study cohort reported having received treatment for ED in the last five years. In UK, longitudinal study including 1162 men with mean age of 59 years were conducted and 37 percent of them receive treatment for ED at the baseline of the study, which was more than in our study [13]. More frequent sauna bathers were also more prone to use medication for ED, but there was no statistically significant difference between sauna bathing groups.…”
Section: Discussioncontrasting
confidence: 57%
“…Total of 14.8 percent of men in our study cohort reported having received treatment for ED in the last five years. In UK, longitudinal study including 1162 men with mean age of 59 years were conducted and 37 percent of them receive treatment for ED at the baseline of the study, which was more than in our study [13]. More frequent sauna bathers were also more prone to use medication for ED, but there was no statistically significant difference between sauna bathing groups.…”
Section: Discussioncontrasting
confidence: 57%
“…Width of boxes and error bars scaled to source type frequency. Grand median 34 represented by dashed line…”
Section: Resultsmentioning
confidence: 99%
“…33 Although descriptions of herbal or over the counter medicines and platelet‐rich plasma injections were infrequent, health professionals must be aware of their limited efficacy and experimental nature to accurately counsel patients who may find this material online. 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with the suggestion that pharmacists see safety as the over-riding concern with supply of over-the-counter or BTC medications [ 15 ]. Indeed, a study suggested that visits to physicians/nurse practitioners significantly increased amongst users following reclassification of Viagra Connect ® [ 16 ]. Our survey also demonstrated that the Viagra Connect ® Pharmacy Checklist was widely utilised (91.9 %), and nearly all pharmacists (96.8 %) found it useful/very useful.…”
Section: Discussionmentioning
confidence: 99%